Batman/Elmer Fudd : the deluxe edition - King, Tom, 1978- (DC Comics, 2025)
"In the first tale by Tom King and Lee Weeks, when Silver St. Cloud is murdered, a trail of clues leads a renowned wabbit hunter to seek vengeance on Bruce Wayne, which doesn't sit well with Wayne's alter ego-Batman! And, in a backup story by King and Byron Vaughns, Batman must outwit Elmer Fudd, who is dead set on claiming a trophy during rabbit...er...bat...rabbit season (stop changing the sign, Bugs!). This deluxe hardcover edition collects both stories in full-color and noir versions and features an introduction by King, a new cover by Weeks, and behind-the-scenes development art by Weeks and Vaughns"--